Effect of re-mating intervals on growth and reproductive performance of rabbits (Bangladesh Journal of Animal Science, 2013)
The aim of this study was to know the effects of postpartum re-mating intervals on reproductive performances of does and growth of kits. Fifteen female New Zealand White crossbred rabbits were divided into three groups of equal numbers. They were re-mated within 24 hours, at 10 days and 28 days postpartum. Animals were individually caged in cells measuring 2'×2'×2'. Does were kept under natural lighting. Plastic nest boxes were supplied to does 3-4 days before parturition. They were reared up to four generation. Litter weight at birth was significantly (p